ROLE OF TYPOMORPHIC FEATURES OF MINERALS IN INTERPRETING ISOTOPIC DATA: AN EXAMPLE OF FLUORITE FROM THE VOZNESENKA ORE DISTRICT - Kupriyanova I.I.; Shpanov E.P.; Kukushkina O.A.; Kuvshinova K.A.; Rassulov V.A.; Belyatsky B.V. (My University, 2004)
An example of fluorite from the Voznesenka Ore District was used to demonstrate the importance of mineralogical studies for interpreting the results of an isotopic research conducted to reveal the age relations between the sources of magmatic rocks and ores. Rb-Sr and Sm-Nd dating was carried out to refine the relative ages of the protolithionite and biotite granites, Nb-Ta and Sn ore mineralization of different types and gabbromonzonitoids. The three isochrons obtained for fluorite in the Li-Be-fluorite ore suggest that the mineralizing processes lasted for a long time. The Rb-Sr and Sm-Nd isotopic systems of the rocks and fluorite indicated that the magmatic rocks and postmagmatic ores of this district contain both crustal and mantle material.